Etika Bermedia Sosial dalam Islam dan Implikasinya terhadap Karakter Muslim - Bobi Saputra; Fito Febrian; Ikbal Maulana; Aziz Faridzqi (International Forum of Researchers and Lecturers, 2026)
The development of social media in the digital age has brought significant changes to society’s communication patterns, including in the lives of Muslims. Social media serves not only as a means of communication but also as a space for shaping individual opinions, behaviors, and character. However, the ease of accessing information has been accompanied by an increase in various problems, such as the spread of misinformation, hate speech, cyberbullying, and a lack of ethical standards in communication. This situation highlights a gap between the use of technology and the application of moral values, particularly from an Islamic perspective. This study aims to analyze social media ethics in Islam and its implications for the character development of Muslims. The method employed is a qualitative approach using a literature review sourced from the Qur’an, Hadith, books, scientific journals, and reports related to social media usage. The research findings indicate that Islam possesses comprehensive principles of communication ethics, such as tabayyun (verification of information), qaulan sadida (truthful speech), qaulan layyina (gentle speech), and prohibitions against backbiting and slander. The application of these principles in social media can shape the character of Muslims to be virtuous, honest, responsible, and wise in their interactions.